2007
DOI: 10.1016/j.molcel.2007.05.002
|View full text |Cite
|
Sign up to set email alerts
|

The Plug Domain of the SecY Protein Stabilizes the Closed State of the Translocation Channel and Maintains a Membrane Seal

Abstract: Proteins are translocated across membranes through a channel that is formed by the prokaryotic SecY or eukaryotic Sec61 complex. The crystal structure of the SecY channel from M. jannaschii revealed a plug domain that appears to seal the channel in its closed state. However, the role of the plug remains unclear, particularly because plug deletion mutants in S. cerevisiae are functional. Here, we demonstrate that plug deletion mutants in E. coli SecY are also functional and even efficiently translocate proteins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
129
0
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(140 citation statements)
references
References 31 publications
8
129
0
3
Order By: Relevance
“…This has been demonstrated experimentally by cysteine cross-linking of the plug with SecE outside the channel (5) and by observing spontaneous channel opening in conductance measurements (6). Accordingly, deletion of the plug domain is also found to have a prl phenotype (28,29).…”
Section: Sec61p Mutations Affect Protein Orientation In Distinct Ways-mentioning
confidence: 88%
See 1 more Smart Citation
“…This has been demonstrated experimentally by cysteine cross-linking of the plug with SecE outside the channel (5) and by observing spontaneous channel opening in conductance measurements (6). Accordingly, deletion of the plug domain is also found to have a prl phenotype (28,29).…”
Section: Sec61p Mutations Affect Protein Orientation In Distinct Ways-mentioning
confidence: 88%
“…Three mutations are exactly at corresponding positions: Asn 65 in E. coli SecY (prlA8914), Ile 191 (prlA200), and Ile 408 (prlA4-2), matching Arg 67 , Thr 185 , and Met 450 , respectively, in Sec61p. In addition, it has very recently been shown that deletion of the plug domain of E. coli SecY has a prl phenotype (28,29). We therefore set out to test our Sec61p mutations for a prl phenotype in yeast.…”
Section: Translocation Efficiency and Stability Of Mutantmentioning
confidence: 99%
“…The signal sequence promotes binding of the preprotein to a cleft of SecA formed by multiple domains, including the preprotein-binding domain and C-terminal domain (5)(6)(7)(8)(9). SecA then targets the preprotein to SecYEG at the membrane, where the signal sequence inserts into a channel formed by SecY (10)(11)(12). SecA also contains two nucleotide-binding domains with ATPase activity.…”
mentioning
confidence: 99%
“…It has been proposed that the inserting signal sequence of the preprotein inserts at a lipid exposed lateral gate between TM2 and TM7 whereupon the clamshell is opened through a widening of the central constriction and a displacement of the plug. The SecYEβ complex of M. jannaschii has been crystallized in an idle state in the absence of the SecA motor domain or the ribosome, and is considered as a resting state, in which the pore is tightly sealed by the central constriction comprises six hydrophobic residues and the plug domain (6). The structure of a SecA-SecYEG complex of Thermotoga maritima suggests a preopen state of the channel with a major movement of the lateral gate helices TM7, TM8, and TM5, and a partial displacement of the plug leaving a narrow gap in the lateral gate of 5 Å (7).…”
mentioning
confidence: 99%